Evaluation of α-glucosidase inhibition, antioxidant and antibacterial effects of Gymnema sylvestre R. Br. - Ghous, Tahseen; Akhtar, Kalsoom; Andleeb, Saiqa; Khizar, Saira; Ali, Shaukat; Mustafa, Rozina Ghulam; Shafique, Irsa; Naseer, Anum (Bangladesh Journal of Botany, 2021)
The results of antioxidant assays with Gymnema sylvestre leaf extracts revealed that methanol, acetone, and aqueous extracts possessed maximum DPPH (83, 83, and 75%) and ABTS scavenging potential (85, 71, and 82%). Chloroform possessed maximum total flavonoid (24.6 mg/100 ml) and total iron contents (435.3 ± 0.0125 mg FeSO4 E/G). The extracts of n-hexane, ethyl acetate, and chloroform of Gymnema sylvestre leaves displayed an IC50 value of 170.2, 44.4, 131.6 μg/ml, respectively in α-glucosidase inhibition assay. Methanol and aqueous extracts showed maximum inhibition of E. ammni (17 ± 2.0 and 19.6 ± 0.57 mm), E. coli (15.3 ± 0.57 and 17.6 ± 0.57 mm), and S. aureus (16.6 ± 1.52 and 19.3 ± 1.15 mm). It may be concluded that all potential effects of G. sylvestre leaf extracts were due to the presence of phytochemical constituents such as flavonoids, steroids, quinones, phenols, triterpenoids, tannins, alkaloids, and saponins. Present findings suggest that these extracts present a satisfactory source for the preparation of antioxidant and antidiabetic medicines.